(Re)conceptualizing Protests: Activism, Resistance, and AANAPISIs - Gutierrez, Rose Ann E.; Le, Annie (Frontiers in Education, 2018)
Though protests on college campuses have captured public attention, far less consideration has been paid to Asian American Native American Pacific Islander Serving Institutions (AANAPISIs). The Asian and Pacific Islander American (APIA) population has historically served on the front lines of the Asian American Movement during the Civil Rights Movement influencing the educational experiences of APIA students. While literature documents student activism from APIA students, they are portrayed as an apolitical group. The purpose of this article is to (re)conceptualize the term protest to capture the historical and contemporary forms of activism by researchers, policy makers, community organizers, and students throughout a decade that pushed a legislation forward to create the federal designation for AANAPISIs. We argue that the term protest is limiting in research. Instead, the term activism should be used in order to encapsulate the ways APIAs have been engaged socially and politically. Additionally, there exists a gap in educational literature discussing how the spatial politics of domination and resistance manifests in representational spaces—in this case institutional structures like AANAPISIs. Influenced by spatial politics and spatial theory we put forth a conceptual argument that the representational existence of AANAPISIs is a site of resistance that needs to be better understood, especially in the era of Trump where anti-immigration and racist rhetoric is ever-present, because of the ways APIAs continue to be racialized and (re)positioned in United States racial discourse and research.